The SARS-CoV-2 Infection Among Students in the University of Porto: A Cross-Sectional Study - Meireles, P (2022)
Objective: We aimed to quantify SARS-CoV-2 specific antibodies’ seroprevalence among university students in Porto. Methods: A rapid point of care testing for SARS-CoV-2 specific immunoglobulin (Ig) M and IgG antibodies was performed, and a questionnaire was applied to 6512 voluntary students from September to December 2020. We computed the apparent IgM, IgG, and IgM or IgG prevalence, and the true prevalence and 95% credible intervals (95% CI) using Bayesian inference. Results: We found an apparent prevalence (IgM or IgG) of 9.7%, the true prevalence being 7.9% (95% CI 4.9–11.1). Prevalence was significantly higher among males (10.9% vs. 9.2%), international students (18.1% vs. 10.4% local vs. 8.8% nationally displaced), and increased with age. Those with a known risk contact, that experienced quarantine, had symptoms, or a previous negative molecular test had a higher seroprevalence. Of the 91 (1.4%) students who reported a molecular diagnosis, 86.8% were reactive for IgM or IgG. Conclusion: Based on immunological evidence infection was 5.6-fold the reported molecular diagnosis. The higher seroprevalence among male, older, and international students emphasizes the importance of identifying particular groups. Copyright © 2022 Meireles, Costa, Novais, Miranda, Lopes, Severo and Barros.